Digital Teaching Materials for Elementary School Social Sciences Learning Courses - Deva Ananta Wijaya; Ni Wayan Rati; I Nyoman Laba Jayanta (Universitas Pendidikan Ganesha, 2023)
Learning activities in lectures tend to be monotonous and use the lecture method, so the impact on learning activities could be more optimal. This research aims to develop digital teaching materials for elementary school social studies subjects. This type of research is developed using the ADDIE model. The subjects of this study were two learning design experts, two learning material experts, and two learning media experts. The test subjects for this study were two lecturers and students, which included three individual test students and nine small group test students. This research data collection method is a questionnaire. The data collection instrument uses a rating scale. The techniques used to analyze the data are descriptive qualitative analysis and quantitative descriptive analysis. The study's results, the assessment of learning material experts, obtained a value of 0.96 with very high content validity qualifications. The assessment given by the learning design expert is 0.94, with very high content validity qualifications. The assessment results from learning media experts were 0.96, with very high content validity qualifications. The practicality test results scored 98.5% (very good). The assessment results of the individual test get a score of 95% (very good). The results of the small group test scored 96.11% (very good). It was concluded that Social Science Learning Digital Teaching Materials were appropriate for use in learning.